Study on Farmers’ Willingness to Participate in High-Standard Farmland Construction Against the Background of Agricultural Green Development - Kexin Zhou; Shaojun Chen; Bing Liang (Land)
Within the context of agricultural green development, the construction of high-standard farmland plays a crucial role in enhancing agricultural productivity, ensuring food security, and achieving sustainable development. However, as the direct participants, farmers’ willingness and enthusiasm to engage in high-standard farmland construction largely determines the success of these initiatives. Therefore, based on data from 326 samples in Qinghai Province, this study employs a structural equation model to analyze the impact of farmers’ cognition and the current condition of farmland on the willingness to participate in high-standard farmland construction and verify the mediating effect of information trust. The results indicate the following: (1) the impact pathways of farmers’ cognition on participation willingness vary across different dimensions, with subjective norms and behavioral attitudes having a direct positive influence, while perceived behavioral control shows no direct effect; (2) the current condition of farmland has a direct and significant negative effect on participation willingness; (3) information trust exhibits varying mediating effects across different pathways, showing a partial mediating effect on behavioral attitudes and subjective norms, a full mediating effect on perceived behavioral control, and a suppressive effect on farmland condition. This study, grounded in the context of China’s green agricultural development goals, provides new insights into the relationship between government policy implementation and farmers’ willingness to participate. It establishes a scientific foundation for policymakers to formulate strategic green development policies.